2018
DOI: 10.1007/s10120-018-0804-3
|View full text |Cite
|
Sign up to set email alerts
|

Total vs proximal gastrectomy for adenocarcinoma of the upper third of the stomach: a propensity-score-matched analysis of a multicenter western experience (On behalf of the Italian Research Group for Gastric Cancer–GIRCG)

Abstract: Although PG for upper third GC showed good results in terms of survival, it is associated with an increased mortality rate and a higher risk of reflux esophagitis and anastomotic stricture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(47 citation statements)
references
References 33 publications
3
38
1
1
Order By: Relevance
“…Group TG PG tant, because, unfortunately, long-term survival is extremely low in gastric cancer patients. The results of the current study were consistent with the findings in the literature, as the time to oral feeding and reaching the target oral calorie intake was observed to be achieved more quickly with fewer problems in the PG group (8,13,22,23). Moreover, since duodenal transit was preserved, the adverse effects of by-passing the duodenum were not documented.…”
Section: Figure 1 Kaplan-meier Survival Curves For Proximal and Totasupporting
confidence: 91%
See 3 more Smart Citations
“…Group TG PG tant, because, unfortunately, long-term survival is extremely low in gastric cancer patients. The results of the current study were consistent with the findings in the literature, as the time to oral feeding and reaching the target oral calorie intake was observed to be achieved more quickly with fewer problems in the PG group (8,13,22,23). Moreover, since duodenal transit was preserved, the adverse effects of by-passing the duodenum were not documented.…”
Section: Figure 1 Kaplan-meier Survival Curves For Proximal and Totasupporting
confidence: 91%
“…The main reason for the number of lymph nodes less than 25 in both groups can be explained by that D1 dissection was applied to seven patients in the TG group and to five patients in the PG group because the intraoperative determination of small peritoneal metastases could not be detected preoperatively with imaging methods. In the literature, many studies have demonstrated that although fewer lymph nodes have been harvested in the PG than the TG, no statistically significant difference was found between the two surgical procedures regarding survival rates; the extent of resection has not affected the outcome once adequate resection margins have been reached (7,9,16,17). The results of these studies were harmonious with our manuscript.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…At the initial point of this study, the control group had not been determined because of the difference in indications between LPG and L-TG. It became clear that the postoperative QOL was similar between L-DT and L-JIP, and some researchers have reported that there were few significant differences in the postoperative QOL between total and proximal gastrectomy [14, 15]. …”
Section: Methodsmentioning
confidence: 99%